Complex arts-based interventions for patients receiving haemodialysis: A realist review. Issue 2 (4th May 2021) - Carswell, Claire; Reid, Joanne; Walsh, Ian; McAneney, Helen; Lee, Jenny Baxley; Noble, Helen
ABSTRACT: Many patients with end-stage kidney disease require haemodialysis, a treatment that requires attending hospital three times a week for four hours each visit. This treatment impacts profoundly on mental health. Arts-based interventions for patients receiving haemodialysis could address the impact of this treatment; however, there is no consensus on methods of implementation and mechanisms underlying these interventions in specific clinical contexts. Using a realist approach, relevant articles were synthesised to inform theory relating to the mechanism and implementation of complex arts-based interventions for haemodialysis patients. The theoretical framework includes two implementation phases, firstly delivery of person-centred art activities during haemodialysis and secondly, display of completed artwork. This intervention triggers mechanisms including flow and social capital. Implementation is hindered by constraints of the haemodialysis unit and patients' lack of confidence in their artistic skills. These issues can be addressed through aflexible approach to implementation and support from healthcare professionals.